2016
DOI: 10.1016/j.bmhimx.2015.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr virus infection of infants: implications of early age of infection on viral control and risk for Burkitt lymphoma

Abstract: Since its first description by Denis Burkitt, endemic Burkitt's lymphoma (BL), the most common childhood cancer in sub-Saharan Africa, has led scientists to search for clues to the origins of this malignancy. The discovery of Epstein-Barr virus (EBV) in BL cells over 50 years ago led to extensive sero-epidemiology studies and revealed that rather than being a virus restricted to areas where BL is endemic, EBV is ubiquitous in the world's population with an estimated greater than 90% of adults worldwide infecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…For example, it has been established that children residing in malaria-endemic regions acquire EBV infection by six months of age on average, compared to those from non-endemic regions, thus implicating P. falciparum as well as EBV in breast milk as a causal factor in EBV transmission or eBL development [ 22 , 67 , 68 ]. Immune-related interactions in malaria and EBV infection share a disease-causal relationship considering that exposure to repeated malarial infections and early ages of EBV infections lead to eBL occurrence [ 24 , 69 , 70 ]. These facts have contributed to studies that aim to establish causal relationships between the two endemic diseases to inform interventions for eBL management [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it has been established that children residing in malaria-endemic regions acquire EBV infection by six months of age on average, compared to those from non-endemic regions, thus implicating P. falciparum as well as EBV in breast milk as a causal factor in EBV transmission or eBL development [ 22 , 67 , 68 ]. Immune-related interactions in malaria and EBV infection share a disease-causal relationship considering that exposure to repeated malarial infections and early ages of EBV infections lead to eBL occurrence [ 24 , 69 , 70 ]. These facts have contributed to studies that aim to establish causal relationships between the two endemic diseases to inform interventions for eBL management [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research has also shown that infants in non-malaria endemic regions of Kenya acquire EBV at the mean age of 8 months and have a lower risk of eBL development [ 22 ]. Collectively, being infected with EBV at an early age is linked to the risk of developing eBL [ 22 24 ]. To address current gaps in knowledge, we examined the relationship between hemoglobinopathies, merozoite surface protein-2 gene polymorphisms, and the acquisition of EBV among infants (0–12 months) in a holoendemic P. falciparum transmission region of western Kenya.…”
Section: Introductionmentioning
confidence: 99%
“…Possible spread via organ transplantation can occur which is of particular concern in association with subsequent infection by EBV [22]. Transmission by milk is also a possible route, but is a non-significant mode of EBV transmission [28].…”
Section: Transmissionmentioning
confidence: 99%
“…Of these malignancies, PEL cells are infected with both EBV (~80%) and KSHV (100%) [4]. In sub-Saharan Africa, both EBV and KSHV infections are very common [5]. Infection with both viruses occurs in childhood, with EBV infection occurring earlier than KSHV [6,7].…”
Section: Introductionmentioning
confidence: 99%